„Umiejscawianie” się studentów w przestrzeni praktykowania – z perspektywy praktyki konstruktywistycznej - Malinowska, Joanna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The starting point for the reflection is the adoption of constructivist vision of pedagogical apprenticeship. In order to meet its objectives, it is necessary for the students to establish themselves within school/kindergarten environment. The space within which the students undergo their apprenticeships explored, described, evaluated and re-constructed by the students. The space processed in such manner becomes tame and domesticated, which is close to Tuan’s conception of place. It is therefore important to recognize whether and how the space becomes a place. Space domestication may also be analysed by taking into account the extent of students’ freedom of action, their unfettered behaviour and their liberty to modify the space. Exploration of the space and the process of placing yourself within it is connected with gaining experience, which is always subjective. Author’s own research carried in this area allows to attempt to answer the following questions: How do students read the space of pedagogical apprenticeship? What sense and meanings do they apply to it? To what extent do the teachers/supervisors contribute to the construction of meanings by students, and to what extent do these teachers contribute to the strengthening of thought patterns?
Keywords: constructivism theory; pedagogical apprenticeship; place; space